Telekom Malaysia Berhad - binti Mohd Noor, Nurul Azlin Syahmi; Kee, Daisy Mui Hung; bt Abdul Rahman, Nurfathin Awatif; bt Abdullah, Najihah; binti Mohamad Fadli, Nurliyana; Mahtre, Sampada (Asia Pacific Journal of Management and Education (APJME), 2019)
Telekom Malaysia Berhad (TM), Malaysia’s Convergence Champion and No. 1 Converged Communications Services Provider offers a comprehensive suite of communication services, mobility, content, Wi-Fi and smart services. As a market leader, TM is driven by stakeholder value creation in a highly competitive environment.(https://www.tm.com.my/Pages/Home.aspx) Telekom Malaysia Berhad also has TM GLOBAL as one of their global company, focusing on domestic and international wholesale business, offering a comprehensive suite of cutting-edge communication services and solutions in connectivity and beyond. Recently, based on our research Telekom Malaysia Berhad’s net profit fell in the second quarter ended June 30, 2018 on lower earnings from its voice and data services. In a filing with Bursa Malaysia today, the fall in voice and data services' profits was affected by the provision recognised for reduction in revenue in view of regulatory mandated access pricing.(New Straits Times)